2013
DOI: 10.2298/aci1302117p
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary injuries associated with pelvic fractures

Abstract: Genitourinary injuries increase overall mortality in patients with pelvic fracture, compared with traumas without associated GU injuries. These patients require multidisciplinary approach, preferably in tertiary institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Pelvic fractures resulting in PFUI are high impact injuries with mortality rates between 5–33% ( 4 , 29 , 32 , 36 , 45 , 48 - 53 ). Other associated injuries are common and include: intracranial (40–66.1%), splenic (9.3–37%), colorectal (6.8–29.1%), bladder (2.5–28%), chest (6–16.6%), liver (5.6–19%), lower limb fracture(s) (17%), pulmonary (9.3%), upper limb fracture(s) (3%) and diaphragmatic rupture (3–21%) ( 4 , 32 , 33 , 39 , 52 , 54 - 58 ). Initial medical management should concentrate on resuscitating and stabilising the patient, and then on identifying all associated injuries.…”
Section: Injuries Associated With Pelvic Fracturesmentioning
confidence: 99%
“…Pelvic fractures resulting in PFUI are high impact injuries with mortality rates between 5–33% ( 4 , 29 , 32 , 36 , 45 , 48 - 53 ). Other associated injuries are common and include: intracranial (40–66.1%), splenic (9.3–37%), colorectal (6.8–29.1%), bladder (2.5–28%), chest (6–16.6%), liver (5.6–19%), lower limb fracture(s) (17%), pulmonary (9.3%), upper limb fracture(s) (3%) and diaphragmatic rupture (3–21%) ( 4 , 32 , 33 , 39 , 52 , 54 - 58 ). Initial medical management should concentrate on resuscitating and stabilising the patient, and then on identifying all associated injuries.…”
Section: Injuries Associated With Pelvic Fracturesmentioning
confidence: 99%
“…Approximately 15% of patients with pelvic fractures have associated bladder or urethral injuries [17]. In our study, one patient in group 1 sustained extraperitoneal urinary bladder rupture without secure repair during the pelvic surgery.…”
Section: Discussionmentioning
confidence: 68%
“…Epidemiologic studies have reported that 12% to 62% of patients with pelvic fractures had additional injuries to the thorax, brain, long bones and abdominal organs to include the genitourinary system, spine and the peripheral nervous system. 21,22 Tomislav Pejcic et al 23 studied urethral injuries in 46% of patients and urinary bladder trauma in 12% of patients. In contrast to us, Nan-Ping Yang et al 1 observed the most common injuries associated with pelvic fractures were fractures of lower limbs (21.50%) followed by fractures of the spine/ trunk (20.97%) and fractures of upper limbs (18.18%), fracture of the skull or intracranial injury (17.59%), internal injury of the abdomen and pelvis (11.00%) and internal injury of the chest (7.20%).…”
Section: Discussionmentioning
confidence: 99%